Differential mucosal tropism and dissemination of classical and hypervirulent Klebsiella pneumoniae infection - Teck-Hui Teo; Nurul N. Ayuni; Michelle Yin; Jun Hao Liew; Jason Q. Chen; Natalia Kurepina; Ravisankar Rajarethinam; Barry N. Kreiswirth; Liang Chen; Pablo Bifani (iScience, 2024)
Summary: Klebsiella pneumoniae (Kp) infection is an important healthcare concern. The ST258 classical (c)Kp strain is dominant in hospital-acquired infections in North America and Europe, while ST23 hypervirulent (hv)Kp prevails in community-acquired infections in Asia. This study aimed to develop symptomatic mucosal infection models in mice that mirror natural infections in humans to gain a deeper understanding of Kp mucosal pathogenesis. We showed that cKp replicates in the nasal cavity instead of the lungs, and this early infection event is crucial for the establishment of chronic colonization in the cecum and colon. In contrast, hvKp replicates directly in the lungs to lethal bacterial load, and early infection of esophagus supported downstream transient colonization in the ileum and cecum. Here, we have developed an in vivo model that illuminates how differences in Kp tropism are responsible for virulence and disease phenotype in cKp and hvKp, providing the basis for further mechanistic study.